2020
DOI: 10.3389/fimmu.2020.569006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of B Cell Clonality and Investigation Into Properties of the IgM in Patients With Schnitzler Syndrome

Abstract: The Schnitzler Syndrome (SchS) is an acquired, autoinflammatory condition successfully treated with IL-1 inhibition. The two main defining features of this late-onset condition are neutrophilic urticarial dermatoses (NUD) and the presence of an IgM monoclonal component. While the former aspect has been extensively studied in this disease setting, the enigmatic paraproteinaemia and its potential consequential effects within SchS, has not previously been thoroughly addressed. Previous studies analyzing clonal B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…It could be postulated that IgM binds to DPP10 leading to aberrant activation of NLRP3. [ 48 ] These findings are interesting yet to be replicated in independent cohorts of patients.…”
Section: Classical Schnitzler Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…It could be postulated that IgM binds to DPP10 leading to aberrant activation of NLRP3. [ 48 ] These findings are interesting yet to be replicated in independent cohorts of patients.…”
Section: Classical Schnitzler Syndromementioning
confidence: 98%
“…However, little to none is known regarding the role of these paraproteins in pathogenesis. Pathak et al [ 48 ] investigated the B cell clonality in ten patients with Schnitzler syndrome. By analyzing the variable, diversity, and junctional segment composition of the immunoglobulin heavy chain and sequencing the complementarity determining region 3, the authors found evidence of clonality of individual patients but failed to demonstrate shared B cell clonality between these patients.…”
Section: Classical Schnitzler Syndromementioning
confidence: 99%
“…However, testing of 30 SchS patient for the p.L265P variant using ASO-PCR technique, which has a detection sensitivity down to 1% of the mutant allele, found that only 9/30 patients carried the p.L265P mutation (43). This finding suggests that somatic MYD88 mutations might have a role in the pathogenesis of SchS but this is unlikely to be a universal mechanism.…”
Section: Schnitzler's Syndrome (Schs)mentioning
confidence: 98%
“…This study found that only 1 out of 6 patients carried pathogenic variants associated with CHIP. The affected patient was found to have 3 mutations: one in DNMT3-A (c.2645G>A p.Arg882His) and two mutations in TET-2 (c.4585C>T p.Gln1529; p.Gln1699*), all with a significant VAF (0.407, 0.388 and 0.402 respectively) (43). These mutations were also associated with allelic skewing, which was determined by testing for X chromosome inactivation.…”
Section: Acquired Nlrp3-associated Autoinflammatory Disease (Nlrp3-aid)mentioning
confidence: 99%
See 1 more Smart Citation